Indigenous Identity Appropriation in Aotearoa New Zealand: The White Academics Who Claim to Be Indigenous Māori and the Māori Who Claim to Be Indigenous Whites - Deane Galbraith (Genealogy)
Unlike in North America, where several “race-shifters”, “Pretendians”, or “self-indigenizers” have been exposed over the last decade, Indigenous identity appropriation has not been publicly exposed or even widely discussed in Aotearoa New Zealand. This study is the first to identify and to describe the methods and motivations of four Pākehā (White) self-indigenizers who are currently working, or were trained, in Aotearoa New Zealand, outlining also the harms they have caused. In addition, this study examines another type of Indigenous identity appropriation taking place in Aotearoa New Zealand, involving a small group of central North Island Māori, whose primary spokesperson is Monica Matāmua. The group claim to be descended from white-skinned Hotu, who they purport had migrated to Aotearoa New Zealand in the 200s B.C., making them the alleged true Indigenous people instead of Māori. Each type of Indigenous identity appropriation provides a range of benefits to those who thereby claim Indigenous status, and this is in part due to the valorization of certain aspects of Indigeneity that occurred from ca. the 1960s to the 1980s. Indigenous identity appropriation has further been encouraged by the backlash against so-called “Māori privilege” that has gathered momentum since ca. the 1980s.